COMPARISON OF ACCURACY AND PRECISION OF DISTANCE READINGS ON HC-SR04, JSN-SR04T, AND A02YYUW ULTRASONIC SENSORS - Akbar Rizki Priadi; Regita Aulia Safitri; Tyo Bima Pratama; Ulinnuha Latifa (TESLA: Jurnal Teknik Elektro, 2025)
Ultrasonic sensors were created to be able to detect distance with ultrasonic sound in the 40 kHZ frequency range. The principle of work is to reflect the signal to the intended object and the results of the reflection will be received by the sensor, then processed to provide readings. Ultrasonic sensors have various types in the market. The importance of accuracy and precision in reading results makes one way to select sensors before use. The purpose of this research is to compare three different types of ultrasonic sensors to determine the level of accuracy and precision of the HC-SR04, JSN-SR04T, and A02YYUW ultrasonic sensors in reading distance. The method used is experimental and previous literature with similar topics. Tests were carried out directly in the room with distance readings between 25-70 cm, each data variation was repeated 5 times. Each sensor tested has its own specifications, especially the JSN-SR04T and A02YYUW sensors can be applied to water or can be labeled waterproof sensors. The test results show that the HC-SR04 sensor has varied distance reading results with accuracy